173k views
5 votes
Plz help it's urgent ​

Plz help it's urgent ​-example-1

1 Answer

2 votes

d)


\frac{2 {x}^(2) - xy + 2xy - {y}^(2) }{6xy - 3 {y}^(2) } = (x(2x - y) + y(2x - y))/(3y(2x - y)) = \\


((x + y)(2x - y))/(3x(2x - y)) = (x + y)/(3x) \\

_________________________________

e)

I think -6 should be +6

or +3x should be -3x


\frac{ {x}^(2) + 2x + x + 2 }{ {x}^(2) + 2x + 3x + 6 } = (x(x + 2) + (x + 2))/(x(x + 2) + 3(x + 2)) = \\


((x + 1)(x + 2))/((x + 3)(x + 2)) = (x + 1)/(x + 3) \\

Or


(x(x + 2) + (x + 2))/(x(x + 2) - 3(x + 2)) = ((x + 1)(x + 2))/((x - 3)(x + 2)) = \\


(x + 1)/(x - 3) \\

_________________________________

f)


\frac{ {a}^(2) - 5a - 4a + 20 }{ {a}^(2) - 5a + 2a - 10 } = (a(a - 5) - 4(a - 5))/(a(a - 5) + 2(a - 5)) = \\


((a - 4)(a - 5))/((a + 2)(a - 5)) = (a - 4)/(a + 2) \\

And we're done.

Thanks for watching buddy good luck.

♥️♥️♥️♥️

User Poliquin
by
4.9k points